Distribution of Cooling Rates in Cylinder Containers with Different Diameters at Crystallisation Stage of Saccharomyces cerevisiae Suspension - Maruschenko, V. V.; Vysekantsev, I. P. (Problems of Cryobiology and Cryomedicine, 2008)
The distribution of cooling rates in S. cerevisiae microorganism suspension in physiological solution under its freezing in cylinder containers with different diameters (10, 20 and 30 mm) with 1, 5 and 10°C/min rates has been determined. Cells, being in different sample’s points at the stage of cell suspension crystallisation, are shown as cooled under very different regimen parameters. This results in a decrease of bioobject’s integrity with the augmentation of samples’ size and cooling rate. There has been established the analytic expression, approximating the temperature field of S. cerevisiae suspension in physiological solution at crystallisation stage in cylinder container, depending on its diameter and cooling rate of container external surface.